Search for the wild animal reservoir of Trypanosoma sp in mammals of N’Djili-Brasseries (Kinshasa, Democratic Republic of Congo) - KABAMBA MWAMBA, Matthieu Willy; TSHILENGE MBUYI, Curé Georges; MALEKANI, J. (IAV Hassan II, 2017)
Durant 6 mois, 201 spécimens de mammifères sauvages représentant 7 espèces réparties en 6 genres, 4 familles et 3 ordres, dont 2 Genetta angolensis, 3 Nandinia binotata, 10 Galagoides demidoff, 35 Protoxerus strangeri, 73 Funisciurus congicus, 15 Rattus rattuset 63 Rattus norvegicus, ont été capturés dans le quartier N’Djili-Brasseries en vue d’identifier le réservoir animal sauvage des trypanosomes. La présente étude a montré par la méthode de la réaction de polymérisation en chaîne, ou Polymerase Chain Reaction (PCR), que de ces sept espèces, seule Rattus rattus et Rattus norvegicus capturées dans le secteur habité par l’homme avaient Trypanosoma brucei gambiense avec une prévalence de 13,3 % pour Rattus rattus et 9,5 % pour Rattus norvegicus, ce qui nous conduit à conclure que ces deux espèces seraient réservoirs de Trypanosoma brucei gambiense. Mots clés: Réservoir, Trypanosoma sp, mammifères, N’Djili-Brasseries, Kinshasa. During 6 months, 201 specimens of wild mammals representing 7 species divided into 6 genera, 4 families and 3 orders, of which 2 Genetta angolensis, 3 Nandinia binotata, 10 Galagoides demidoff, 35 Protoxerus strangeri, 73 Funisciurus congicus, 15 Rattus rattus and 63 Rattus norvegicus, were captured at N’Djili- Brasserie to identify the wild animal reservoir of trypanosoma. This study revealed by using the method of polymerase chain reaction (PCR) that among these seven species, only Rattus rattus and Rattus norvegicus, captured in the area inhabited by man, had Trypanosoma brucei gambiense with a prevalence of 13.3 % for Rattus rattus and 9.5 % for Rattus norvegicus. This lead us to conclude that these two species would be reservoir of Trypanosoma brucei gambiense. Keywords: Reservoir, Trypanosoma sp, mammals, N’Djili-Brasseries, Kinshasa.